«In Dreams the Soul Travels Everywhere, and Sometimes Back to Our Small Native Land»: the Language of Dreams of Representatives of the Chuvash and Mari Diasporas of the Moscow Region - Marina V. Kutsaeva (Этническая культура, 2022)
The article deals with one of the most interesting and fairly unstudied functions of the ethnic language in the conditions of the internal diaspora – the language of dreams. Based on the data of her own field research, the author’s goal is to identify the topics and situations in which the representatives fix their dreams in their ethnic languages. In the present article the author uses the data obtained as a result of the sociolinguistic surveys conducted in two diasporas of the Moscow region: the Chuvash diaspora (the sample was 100 people) in 2014–2017, and in the Mari diaspora (the sample included 106 people) in 2019–2021. Both surveys were devoted to identifying and describing the functioning of the ethnic language, its interaction with the Russian language in the context of the multilingual and multicultural space of the Moscow region. The results, obtained in the surveys, reveal that 27% of respondents in the Chuvash sample and 49% in the Mari in the first generation have dreams in their respective ethnic languages. These dreams are closely correlated, according to the respondents, fluent speakers, with the subject of dreams and are associated with relatives and friends in their small homeland (often with deceased ancestors), with a certain place or event in the small homeland. In addition, dreams in «their» language also come in emotionally loaded situations, for example, in a state of stress. Respondents with a poor command of an ethnic language (natives of urban settings, as well as the majority of second-generation representatives in the sample) practically do not record dreams in their ethnic language. The author concludes that this particular function is deeply connected with some other functions, such as a communicative or a sacred one in addition, it reflects certain linguistic ideologies that are discretely dominant in these linguistic communities.